2019
DOI: 10.1097/sla.0000000000003627
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Risks of Sleeve Gastrectomy Versus Roux-en-Y Gastric Bypass Among Patients With Chronic Kidney Disease

Abstract: Objective: To determine whether patients with CKD experience higher rates of perioperative complications after RYGB compared to sleeve gastrectomy. Summary of Background Data: For obese CKD patients who qualify for bariatric surgery, sleeve gastrectomy is often preferred to RYGB based on perceptions of prohibitively-high perioperative risks surrounding RYGB. However, some patients with CKD are not candidates for sleeve gastrectomy and the incremental in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Our results are comparable with those of other international studies. In the study by Montgomery et al [13], the same results were shown regarding the overall rate of intraoperative and postoperative complications. This is also true for the study by Topart et al [14] and the randomized trial by Helmiö et al [15].…”
Section: Discussionsupporting
confidence: 56%
“…Our results are comparable with those of other international studies. In the study by Montgomery et al [13], the same results were shown regarding the overall rate of intraoperative and postoperative complications. This is also true for the study by Topart et al [14] and the randomized trial by Helmiö et al [15].…”
Section: Discussionsupporting
confidence: 56%
“…This practice was previously driven by short-term concerns that these patients are of prohibitive surgical risk . However, work suggests that surgical complication rates are low and comparable with patients without end-stage kidney disease . Long-term concerns remain, arising from disagreement between the potential benefits of bariatric surgery and the obesity paradox, an observation that patients undergoing dialysis with higher body mass index actually have lower all-cause mortality .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of LSG have reported success rates of 56% at a mean of 92 days to the same limit [14], and 100% success in a smaller cohort within three months, from a lower mean initial BMI (38.8 kg/m 2 ) [6]. The major complication rate (2.5%) in this cohort is lower than 7.06%, previously published for haemodialysis patients [17], and the overall complication rate of 11.3% is slightly lower than the combined surgical and medical complication rate of 6.2 + 8.3% for CKD patients from the MBSAQIP database [18]. This demonstrates the effectiveness, efficiency and relatively safety of LSG in helping patients become eligible for the kidney transplant waiting list.…”
Section: Discussionmentioning
confidence: 91%